2015
DOI: 10.1080/00268976.2015.1029029
|View full text |Cite
|
Sign up to set email alerts
|

Freezing point depression in model Lennard-Jones solutions

Abstract: Crystallisation of liquid solutions is of uttermost importance in a wide variety of processes in materials, atmospheric and food science. Depending on the type and concentration of solutes the freezing point shifts, thus allowing control on the thermodynamics of complex fluids. Here we investigate the basic principles of solute-induced freezing point depression by computing the melting temperature of a Lennard-Jones fluid with low concentrations of solutes, by means of equilibrium molecular dynamics simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Colligative properties depend only on the properties of the solvent; in other words, freezing point depression is only associated with the solute concentration in the solution, irrespective of the chemical nature of the solute. , The freezing point depression observed in salt solutions at atmospheric pressure can be directly applied in modeling the natural gas hydrate system . In the present work, we calculated the freezing point depression of CH 4 hydrate in the presence of TMAB, TEAB, or TPrAB using the following equation, , where Δ T f is the freezing point depression, T f (solution) is the freezing point of the solution, T f (solvent) is the normal freezing point of the pure solvent, i is the number of ions in the solute (2 in this case), K f is the cryoscopic constant for the solvent, and m s is molality (moles of solute per kilogram of solvent)the concentration of the solution. Over a pressure range of approximately 4–10 MPs, the freezing point depression of CH 4 hydrate in the presence of 5.44 wt % NaCl ( m s = 0.984 mol/kg water) was found to be about 2.30 K, so K f of the solvent (water with dissolved methane) was determined to be approximately 1.17 K kg/mol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colligative properties depend only on the properties of the solvent; in other words, freezing point depression is only associated with the solute concentration in the solution, irrespective of the chemical nature of the solute. , The freezing point depression observed in salt solutions at atmospheric pressure can be directly applied in modeling the natural gas hydrate system . In the present work, we calculated the freezing point depression of CH 4 hydrate in the presence of TMAB, TEAB, or TPrAB using the following equation, , where Δ T f is the freezing point depression, T f (solution) is the freezing point of the solution, T f (solvent) is the normal freezing point of the pure solvent, i is the number of ions in the solute (2 in this case), K f is the cryoscopic constant for the solvent, and m s is molality (moles of solute per kilogram of solvent)the concentration of the solution. Over a pressure range of approximately 4–10 MPs, the freezing point depression of CH 4 hydrate in the presence of 5.44 wt % NaCl ( m s = 0.984 mol/kg water) was found to be about 2.30 K, so K f of the solvent (water with dissolved methane) was determined to be approximately 1.17 K kg/mol.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 The freezing point depression observed in salt solutions at atmospheric pressure can be directly applied in modeling the natural gas hydrate system. 82 In the present work, we calculated the freezing point depression of CH 4 hydrate in the presence of TMAB, TEAB, or TPrAB using the following equation, 83,84…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MAS NMR studies on tightly packed protein crystals showed that the bulk water did not completely freeze until below À15 C, whereas crystal waters remained unfrozen until À25 C (42). One mechanism likely contributing to the observed freezing point reduction is a concentration-based effect, as is typically used to explain the dose-dependent effect of solutes on the freezing point of their solvent (46). Earlier studies have also discussed confinement effects, sometimes also referred to as capillary effects (42,47,48).…”
Section: Freezing Of Water Under Mas Nmr Conditionsmentioning
confidence: 99%